Competition between Anion-Deficient Oxide and Oxyhydride Phases during the Topochemical Reduction of LaSrCoRuO 6 - Liang, Z; Batuk, M; Orlandi, F; Manuel, P; Hadermann, J; Hayward, MA (American Chemical Society, 2024)
Binary metal hydrides can act as low-temperature reducing agents for complex oxides in the solid state, facilitating the synthesis of anion-deficient oxide or oxyhydride phases. The reaction of LaSrCoRuO6, with CaH2 in a sealed tube yields the face-centered cubic phase LaSrCoRuO3.2H1.9. The reaction with LiH under similar conditions converts LaSrCoRuO6 to a mixture of tetragonal LaSrCoRuO4.8H1.2 and cubic LaSrCoRuO3.3H2.13. The formation of the LaSrCoRuO x H y oxyhydride phases proceeds directly from the parent oxide, with no evidence for anion-deficient LaSrCoRuO6–x intermediates, in contrast with many other topochemically synthesized transition-metal oxyhydrides. However, the reaction between LaSrCoRuO6 and LiH under flowing argon yields a mixture of LaSrCoRuO5 and the infinite layer phase LaSrCoRuO4. The change to all-oxide products when reactions are performed under flowing argon is attributed to the lower hydrogen partial pressure under these conditions. The implications for the reaction mechanism of these topochemical transformations is discussed along with the role of the hydrogen partial pressure in oxyhydride synthesis. Magnetization measurements indicate the LaSrCoRuO x H y phases exhibit local moments on Co and Ru centers, which are coupled antiferromagnetically. In contrast, LaSrCoRuO4 exhibits ferromagnetic behavior with a Curie temperature above 350 K, which can be rationalized on the basis of superexchange coupling between the Co1+ and Ru2+ centers.